Prospects of common biomolecules as coating substances for polymeric biomaterials. Issue 85 (16th September 2015) - Balaji, A.; Jaganathan, S. K.; Vellayappan, M. V.; John, A. A.; Subramanian, A. P.; SelvaKumar, M.; Mohandas, H.; M, Sundar Raj; Supriyanto, Eko
<x xml:space="preserve">Abstract</x> The concept of using common biomolecules like proteins, carbohydrates, etc., for improving the biocompatibility seems rational and effective because of the bio-friendly surface that they present, remains closer in mimicking the innate environment.